Evolutionary Design of Adjustable Six-Linkage Bar Manufacturing Mechanisms Using Niche Genetic Algorithms - Chiu-Hung Chen; Jyh-Horng Chou (IEEE Access, 2016)
This paper studies the optimal synthesis design of adjustable six-linkage mechanisms in metal-mold die-casting systems. The synthesis process is extremely complex because of higher order structures, collision-free constraints, and multiple loci in the solution space. Therefore, a twin-space crowding genetic algorithm was used to solve the design problem with the multiplicity of solutions. To verify the effectiveness of the proposed approach, this paper first studied the function generation problems for adjustable four linkage-bar structures in the literature, and compared these with a numerical local optimization method. From the comparison result, multiple and more precise design solutions can be obtained with the proposed approach. The synthesis design problem for collision-free adjustable six-linkage bars was then solved and discussed. The simulated experiments demonstrated the promising result of the proposed approach.